2021
DOI: 10.1002/hep4.1721
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of Differentiation 44 Promotes Liver Fibrosis and Serves as a Biomarker in Congestive Hepatopathy

Abstract: Congestive hepatopathy (CH) with chronic passive congestion is characterized by the progression of liver fibrosis without prominent inflammation and hepatocellular damage. Currently, the lack of reliable biomarkers for liver fibrosis in CH often precludes the clinical management of patients with CH. To explore fibrosis biomarkers, we performed proteome analysis on serum exosomes isolated from patients with CH after the Fontan procedure. Exosomal cluster of differentiation (CD)44 levels were increased in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…However, it is not proven to date that the same sequence is applicable for the progression of congestive liver disease. As we showed in this study and reported previously, [ 41 ] lesser degree of inflammation is obvious in the occurrence of fibrosis and tumor in this model. The possibility of distinct usage of S1PR subtypes involved in fibrosis or tumorigenesis, as we showed in this study, should raise concerns for the need of specification of molecular pathways in this entity of disease.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is not proven to date that the same sequence is applicable for the progression of congestive liver disease. As we showed in this study and reported previously, [ 41 ] lesser degree of inflammation is obvious in the occurrence of fibrosis and tumor in this model. The possibility of distinct usage of S1PR subtypes involved in fibrosis or tumorigenesis, as we showed in this study, should raise concerns for the need of specification of molecular pathways in this entity of disease.…”
Section: Discussionsupporting
confidence: 90%
“…To achieve this concentration, we treated HA-administered mice with 10 mg/kg of Hermes-1 or isotype-matched immunoglobulin (IgG2a) twice a week. 38 As anticipated, the anti-CD44 antibody significantly reduced the number of EMD lesions per mouse from 1.38 ± 0.74 to 0.50 ± 0.76 ( P = .02191) ( Figure 3 F-G; supplemental Figure 4 B).
Figure 3.
…”
Section: Resultssupporting
confidence: 72%
“…Beginning 4 weeks after transplantation, mice were administered 10 mg/kg of isotype-matched immunoglobulin (IgG) or the anti-CD44 antibody Hermes-1 (Anti-CD44) along with 50 μg/kg HA twice a week for an additional 4 weeks. 38 Representative overlay photographs taken by the IVIS-CT Imaging System on Day 70 are shown with the location of the intramedullary tumors, splenic tumors, and EMD lesions. (G) The numbers of EMD lesions in each mouse were counted.…”
Section: Resultsmentioning
confidence: 99%
“…Hyaluronic acid is a member of the extracellular matrix and is deposited in the fibrotic liver 14 . Serum hyaluronic acid is one of the markers of severe hepatic fibrosis and cirrhosis 15 , and in the liver, CD44 is expressed in hepatic stellate cells which are closely related to hepatic fibrosis 16 . In severe lung fibrosis, CD44 regulates the invasive phenotype of fibroblasts through hyaluronic acid 17 .…”
Section: Introductionmentioning
confidence: 99%